PATIENTS VISITING INTENTION: A PERSPECTIVE OF INTERNAL AND SOCIAL MEDIA MARKETING IN KAMBANG JAMBI HOSPITAL - YULHASMIDA YULHASMIDA; SYAHMARDI YACOB; TONA AURORA LUBIS (Management Department, Faculty of Economics and Business, Universitas Jambi, 2019)
In the digital era, the use of the internet is a necessity. The role of social media should be utilized as well as a means of cheap promotion for hospitals. This quantitative study aims to examine the effect of internal marketing on social media, the effect of internal marketing on the interest of patient visits, and the effect of social media on the interest of patient visit Kambang Hospital in Jambi. The respondents involved in this study were all employees in Kambang Hospital, totaling 251 people. Moreover, the questionnaire was distributed by utilizing the google doc application so that the data was immediately tabulated. Additionally, the results of the study were tested using the Smart PLS 2.0 application. As 181 (72%) respondents responded the questionnaires on 13 indicators of internal marketing (IM) variable, 4 indicators of social media (SM) variable and 4 indicators of patient visit interest (PTI) variable. In brief, the results of the study proved that; 1) there was the significant effect of IM on the Constitutional Court, 2) there was the significant effect of IM on SM, 3) there was the significant effect of SM on the Constitutional Court, and 4) there was indirect effect of IM on PTI through SM by using significant Sobel test calculations. This indicated that internal marketing can affect the interest of patient visits through the use of social media.